Caractérisation de la qualité bactériologique d’un poisson frais Rouget barbet de vase (Mullus barbatus) (Linnaeus, 1758) pêché dans la baie de Mostaganem - Si afif, Fatma; Soualmi, Chaimaa (My University, 2024)
Hygiene is a determining factor in the sanitary quality of fish. As it is a highly perishable matrix, the objective evaluation of its hygienic quality is essential for operators in the sector as well as for inspection services and consumers. The issue of this study focuses on evaluating the bacteriological quality of red mullet (Mullus barbatus) (Linnaeus, 1758) caught off the coast of Mostaganem, and its compliance with current sanitary standards. Given the potential risks to public health associated with the consumption of contaminated fish, it is crucial to determine the level of microbial contamination of this prized species and identify factors that may influence its hygienic quality. To evaluate our research, three samples, each composed of five sampling units of red mullet, were collected over three months (March, April, and May 2024) from two ports: Salamandre port and the small port. The results showed fecal contamination, with an abundance of total coliforms varying between 0.375×10² cfu/g and 9.15×103 cfu/g, and fecal coliforms between 0.5×10² cfu/g and 5.5×10² cfu/g, exceeding the reference threshold of 10 cfu/g. However, there was an uncountable presence of coagulase-positive Staphylococci. In parallel, we recorded a total absence of Salmonella in all analyzed samples. In general, the analyzed red mullets present an unsatisfactory microbiological quality.
Keywords: Contamination; hygiene; Mostaganem; Mullus barbatus; Small port; Port of Salamandre